Mesenchymal Stem Cell Administration Attenuates Colon Cancer Progression by Modulating the Immune Component within the Colorectal Tumor Microenvironment. (19th November 2018) - François, Sabine; Usunier, Benoit; Forgue‐Lafitte, Marie‐Elisabeth; L'Homme, Bruno; Benderitter, Marc; Douay, Luc; Gorin, Norbert‐Claude; Larsen, Annette K.; Chapel, Alain
Abstract: We here determine the influence of mesenchymal stem cell (MSC) therapy on the progression of solid tumors. The influence of MSCs was investigated in human colorectal cancer cells as well as in an immunocompetent rat model of colorectal carcinogenesis representative of the human pathology. Treatment with bone marrow (BM)‐derived MSCs significantly reduced both cancer initiation and cancer progression by increasing the number of tumor‐free animals as well as decreasing the number and the size of the tumors by half, thereby extending their lifespan. The attenuation of cancer progression was mediated by the capacity of the MSCs to modulate the immune component. Specifically, in the adenocarcinomas (ADKs) of MSC‐treated rats, the infiltration of CD68+ monocytes/macrophages was 50% less while the presence of CD3+ lymphocytes increased almost twofold. The MSCs reprogrammed the macrophages to become regulatory cells involved in phagocytosis thereby inhibiting the production of proinflammatory cytokines. Furthermore, the MSCs decreased NK (Natural Killer) and rTh17 cell activities, Treg recruitment, the presence of CD8+ lymphocytes and endothelial cells while restoring Th17 cell activity. The expression of miR‐150 and miR‐7 increased up to fivefold indicating a likely role for these miRNAs in the modulation of tumor growth. Importantly, MSC administration limited the damage of healthy tissues and attenuated tumor growth following radiotherapy. Taken together, we here show that that MSCs have durable action on colon cancer development by modulating the immune component of the tumor microenvironment. In addition, we identify two miRNAs associated with the capacity of MSCs to attenuate cancer growth.Stem Cells Translational Medicine 2019;8:285&300 Abstract : After fractionated irradiation, mesenchymal stem cell administration inhibited residual tumor growth, protected healthy tissue. Mesenchymal stem cells modified the immune profile in tumor microenvironment and in irradiated healthy tissue by reprogramming resident cells. These findings support the use of mesenchymal stem cell administration for treatment of severe radiation damage in patients.